Time gated ion microscopy of light-atom interactions. (24th January 2018) - Tzallas, P; Bergues, B; Rompotis, D; Tsatrafyllis, N; Chatziathanassiou, S; Muschet, A; Veisz, L; Schröder, H; Charalambidis, D
Abstract: The development of ultra-short intense laser sources in the visible and extreme ultraviolet (XUV) spectral range has led to fascinating studies in laser-matter interactions and attosecond science. In the majority of these studies, the system under investigation interacts with a focused light beam, which ionizes the system. The ionization products are usually measured by devices, which spatiotemporally integrate the ionization signal originating from the entire focal area, discarding in this way valuable information about the ionization dynamics that take place in the interaction volume. Here, we review a recently developed approach in measuring the spatially resolved photoionization yields resulting from the interaction of infrared (IR)/XUV ultra-short light pulses in gas phase media. We show how this approach enables (a) the in situ focus diagnostic, (b) quantitative studies of linear and non-linear ionization processes in the IR/XUV regime, (c) single-shot XUV-pump-XUV-probe studies and (d) single-shot 2nd-order XUV autocorrelation measurements.